Paphiopedilum notatisepalum, a new species of slipper orchid (Cypripedioideae, Orchidaceae) from China based on morphological and DNA evidence - Wang, Meina; Lan, Si-Ren; Liu, Zhong-Jian (Phytotaxa, 2017)
A new species of Paphiopedilum (Orchidaceae) from Yunnan, China, is described and illustrated based on morphological and molecular evidence. Morphological comparisons indicate that the new species P. notatisepalum is highly similar to P. henryanum, from which it differs by its leaves with large yellow spots, shorter scape, larger flower, ovate, white sepals and petals that are pale purple-red with large purple spots and yellow-white margins. Molecular analyses of combined nuclear and plastid datasets (nrITS and matK) indicate that P. notatisepalum is sister to P. barbigerum, which has a green leaves and pale yellow-green sepals and petals. The morphological and molecular evidence support the hypothesis that P. notatisepalum is a new species.